Perceptions of Trees Outside Forests in Cattle Pastures: Land Sharing Within the Central Volcanic Talamanca Biological Corridor, Costa Rica - Sibelet, Nicole; Chamayou, Lucile; Newing, Helen; Gutiérrez Montes, Isabel A. (Springer Link, 2019)
Trees outside forests can play an important role in production and conservation and increase connectivity within agricultural landscapes. However, farmers’ perceptions of the trees and the values they place on them will determine the extent to which they will do so in the future. In a case study in Costa Rica, northwest of the Central Volcanic Talamanca Biological Corridor, we conducted 42 semi-structured interviews with farmers and other key informants. Results show that farmers maintain trees on their land and attribute to them diverse values (technical, economic, ecological, social, cultural, aesthetic, and heritage). Farmers reported limitations to the maintenance of trees (lack of financial capital, labour, land area, technical assistance, and adapted species). In addition to potentially unsustainable Payments for Environmental Services, there is scope for more collaborative approaches to conserving the trees built on existing farmer practices.